Early Resistance of Interleukin-10 Knockout Mice to Acute Systemic Candidiasis - Vazquez-Torres, Andres (American Society for Microbiology, 1999)
In contrast to immunocompetent controls, interleukin-10 (IL-10) knockout (KO) mice eliminated an experimental intravenous inoculation with Candida albicans from their kidneys. Improved clearance of C. albicans from the kidneys of IL-10 KO mice was evident at 24 h after intravenous challenge with the fungus. Conversely, mice with a deletion of the IL-4 cytokine gene were more susceptible to systemic candidiasis than were immunocompetent controls. The hyperresistance of IL-10 KO mice to acute systemic candidiasis did not seem to correlate with nitric oxide-mediated immunity, but rather, it appeared to be associated with more efficient effector function of innate cells, possibly neutrophils. In support of the latter hypothesis, we observed that neutrophils from IL-10 KO mice were more efficient at killing C. albicans blastoconidia and hyphae than were neutrophils from immunocompetent control mice. Neither IL-10 KO nor IL-4 KO mice that were monoassociated with C. albicans for 4 weeks showed any histologic evidence of systemic candidiasis of endogenous origin. In contrast to systemic candidiasis, we observed no significant (P < 0.05) differences in susceptibility among IL-10 KO, IL-4 KO, and wild-type (immunocompetent) mice to orogastric candidiasis. Our results suggest that IL-10 exerts a negative effect on the early, innate response to acute systemic candidiasis; however, in comparison to immunocompetent control (wild-type) mice, neither IL-10 nor IL-4 deficiency enhanced susceptibility to orogastric candidiasis.